2005
DOI: 10.1007/s00059-005-2623-7
|View full text |Cite
|
Sign up to set email alerts
|

Perkutane intramyokardiale Implantation von autologen Myoblasten bei ischämischer Kardiomyopathie

Abstract: Transcatheter transplantation of autologous skeletal myoblasts for severe left ventricular dysfunction in postinfarction patients is feasible, safe and promising and, thus, warrants the scrutiny of larger randomized double-blind multi-center trials with longer follow-up surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In line with the findings of trans-epicardial myoblast administration, an increased occurrence of cardiac arrhythmias was observed following transendocardial delivery, emphasizing the need for prophylactic ICD implantation [82,83,186,[189][190][191]. Nonetheless, these small-sized clinical studies suggested that trans-coronary-venous [186] and transendocardial [82,83,[189][190][191][192] cell delivery of skeletal myoblasts was associated with improvements in cardiac performance and clinical symptoms. The SEISMIC study [193] is a relatively small open-label randomized study in which patients were randomized to receive either skeletal myoblasts by trans-endocardial injection or optimal medical treatment.…”
Section: Skeletal Myoblasts Therapysupporting
confidence: 69%
“…In line with the findings of trans-epicardial myoblast administration, an increased occurrence of cardiac arrhythmias was observed following transendocardial delivery, emphasizing the need for prophylactic ICD implantation [82,83,186,[189][190][191]. Nonetheless, these small-sized clinical studies suggested that trans-coronary-venous [186] and transendocardial [82,83,[189][190][191][192] cell delivery of skeletal myoblasts was associated with improvements in cardiac performance and clinical symptoms. The SEISMIC study [193] is a relatively small open-label randomized study in which patients were randomized to receive either skeletal myoblasts by trans-endocardial injection or optimal medical treatment.…”
Section: Skeletal Myoblasts Therapysupporting
confidence: 69%
“…The myoblast cellular graft was intramyocardially injected into the targeted treatment region utilising the MyoCath ™ catheter delivery system under fluoroscopic guidance as previously described. 5 The treatment group received a dose in the range of 150-800 million cells, dependent on the size of ventricular scar tissue to be treated. Since the cell concentration was maintained at 50 million cells/mL, the final number of injections varied per patient.…”
Section: Quadriceps Muscle Biopsy and Cell Culture Expansion And Tranmentioning
confidence: 99%
“…Exciting results of the experimental studies have led to clinical studies which demonstrated benefit of the stem cells on left ventricular functions after acute myocardial infarction or ischemic cardiomyopathy (Chachques et al 2004;Schuster et al 2004;Ince et al 2005). Being accepted as an effective and safe way of performing stem cells into infarcted myocardial region, intracoronary infusion has become a preferable route in particularly acute MI patients (Chen et al 2004;Fernandez-Aviles et al 2004).…”
Section: Discussionmentioning
confidence: 99%